Rough Set Granularity in Mobile Web Pre-Caching - Sulaiman, Sarina; Shamsuddin, Siti Mariyam; Sulaiman, Shahida; Abraham, Ajith
Mobile Web pre-caching (Web prefetching and caching) is an explication of performance enhancement and storage limitation ofmobile devices.